Skeletal Muscle Disorders: A Noncardiac Source of Cardiac Troponin T. Issue 24 (7th April 2022) - du Fay de Lavallaz, Jeanne; Prepoudis, Alexandra; Wendebourg, Maria Janina; Kesenheimer, Eva; Kyburz, Diego; Daikeler, Thomas; Haaf, Philip; Wanschitz, Julia; Löscher, Wolfgang N.; Schreiner, Bettina; Katan, Mira; Jung, Hans H.; et al.
Abstract : Background: Cardiac troponin (cTn) T and cTnI are considered cardiac specific and equivalent in the diagnosis of acute myocardial infarction. Previous studies suggested rare skeletal myopathies as a noncardiac source of cTnT. We aimed to confirm the reliability/cardiac specificity of cTnT in patients with various skeletal muscle disorders (SMDs). Methods: We prospectively enrolled patients presenting with muscular complaints (≥2 weeks) for elective evaluation in 4 hospitals in 2 countries. After a cardiac workup, patients were adjudicated into 3 predefined cardiac disease categories. Concentrations of cTnT/I and resulting cTnT/I mismatches were assessed with high-sensitivity (hs-) cTnT (hs-cTnT–Elecsys) and 3 hs-cTnI assays (hs-cTnI–Architect, hs-cTnI–Access, hs-cTnI–Vista) and compared with those of control subjects without SMD presenting with adjudicated noncardiac chest pain to the emergency department (n=3508; mean age, 55 years; 37% female). In patients with available skeletal muscle biopsies, TNNT/I1-3 mRNA differential gene expression was compared with biopsies obtained in control subjects without SMD. Results: Among 211 patients (mean age, 57 years; 42% female), 108 (51%) were adjudicated to having no cardiac disease, 44 (21%) to having mild disease, and 59 (28%) to having severe cardiac disease. hs-cTnT/I concentrations significantly increased from patients with no to those with mild and severe cardiac disease for all assays (all P <0.001). hs-cTnT–Elecsys concentrations were significantly higher in patients with SMD versus control subjects (median, 16 ng/L [interquartile range (IQR), 7–32.5 ng/L] versus 5 ng/L [IQR, 3–9 ng/L]; P <0.001), whereas hs-cTnI concentrations were mostly similar (hs-cTnI–Architect, 2.5 ng/L [IQR, 1.2–6.2 ng/L] versus 2.9 ng/L [IQR, 1.8–5.0 ng/L]; hs-cTnI–Access, 3.3 ng/L [IQR, 2.4–6.1 ng/L] versus 2.7 ng/L [IQR, 1.6–5.0 ng/L]; and hs-cTnI–Vista, 7.4 ng/L [IQR, 5.2–13.4 ng/L] versus 7.5 ng/L [IQR, 6–10 ng/L]). hs-cTnT–Elecsys concentrations were above the upper limit of normal in 55% of patients with SMD versus 13% of control subjects ( P <0.01). mRNA analyses in skeletal muscle biopsies (n=33), mostly (n=24) from individuals with noninflammatory myopathy and myositis, showed 8-fold upregulation of TNNT2, encoding cTnT (but none for TNNI3, encoding cTnI) versus control subjects (n=16, P Wald <0.001); the expression correlated with pathological disease activity ( R =0.59, P t-statistic <0.001) and circulating hs-cTnT concentrations ( R =0.26, P t-statistic =0.031). Conclusions: In patients with active chronic SMD, elevations in cTnT concentrations are common and not attributable to cardiac disease in the majority. This was not observed for cTnI and may be explained in part by re-expression of cTnT in skeletal muscle. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03660969.